COVID 19 in the Global South: Impacts and Responses. - Carmody, Padraig (Bristol University/Policy Press in Association with the Development Studies Association of Ireland, 2020)
The world has been convulsed by the COVID- 19 (coronavirus disease 2019) pandemic. The virus has caused untold misery both directly and indirectly to people around the world and its effect on societies and economies globally has been catastrophic. International travel has ground to a near halt, the global economy has stalled and many countries around the world are in government- enforced ‘lockdowns’. Numerous countries have entered deep recessions and many global value chains have experienced massive disruption as a result of both demand, and in some cases, supply shocks, sending reverberations through the value chains of suppliers with negative multiplier and accelerator effects. Such economic shocks are largely an outcome of government policy responses to the pandemic and will have cascading effects both socially and economically for many years to come (OECD, 2020). Notwithstanding the billions of lives that have been adversely affected and the hundreds of thousands of deaths resulting from it, the pandemic has also exposed further serious flaws in the architecture of international development.In the Global North, the purpose of lockdowns has been to slow the spread of the disease and prevent healthcare systems from being overwhelmed. The countries of the Global South appear to be affected differently, although this is changing as the geographic epicentres of the disease shift. In the developing world, lockdowns were put in place quickly, with often severe livelihood consequences given high levels of dependence on the informal sector for survival, and the general absence of widespread health, social security and public policy assistance measures. Thus, the ‘secondary effects’ of the crisis are more evident in the Global South, although many countries, as of mid- 2020, have now lifted their lockdowns. These countries are also particularly vulnerable to systemic, structural effects (Hulme and Horner, 2020) and their amplification through interaction with wider contradictions and tendencies.Proponents of unregulated global economic integration argue that this model is universally beneficial for all market participants. However, COVID- 19, along with the previous ‘global’ financial crisis and the coming climate one exposes the contradictions and vulnerabilities of unmanaged interconnection. In a sense we can view connection as contradictory, temporally, as it generated economic growth, but is now associated with synchronized worldwide economic downturn – the most severe since the Great Depression. The contagion of COVID- 19 was mirrored by the financial contagion in the first decade of the 21st century. This in turn has been layered upon more regionally specific crises, such as the persistent developing world debt crisis and adverse effects of the International Monetary Fund/ World Bank structural adjustment programmes, which eviscerated healthcare and education systems in the countries in which they were imposed. A widely applied model of austerity in the aftermath of the North Atlantic financial crisis of 2008 further undermined many attempts at socioeconomic development around the world.The so- called ‘secondary impacts’ of the pandemic in the Global South then are all the more severe as a result of the layering of cumulative crises, like a palimpsest, in Least Developed Countries (LDCs). This is most visible in the predominant economic form that exists in LDCs, the informal economy. Indeed, if we include subsistence agriculture as part of this, more than 85 per cent of the labour force in Africa, for example, are found in that sector. This is partly a result of the hollowing out of the formal sector (both public and private) arising from the aforementioned processes of globalization (debt, enforced adjustment and austerity). The marginal productivity of labour in the informal sector is low and so people who work in it tend not to have much in the way of savings, leaving them vulnerable to shocks such as COVID- 19 and the inability to earn a living in life under state lockdown. At the same time, the dominance of the informal sector makes for low tax returns across the Global South and the consequent under- funding of health and social care systems. For example, China’s donation of four ventilators to South Sudan during the pandemic reportedly trebled the number available in that country and ten African countries were reported to have no ventilators at all (McLean and Marks, 2020). Thus, crisis compounds crisis and systemic vulnerability is accentuated by exposure to and incorporation into a global system characterized by combined and uneven development.This collection explores a number of the issues that arise for the Global South in the grip of a global pandemic. Contributors have been drawn from various sectors and contexts and have specialist knowledge of a range of issues relevant to the impact of this pandemic on the Global South. Contributors focus on the medical impacts, gender equality, migration, economic inequality and (among other issues) the accentuated risks faced by vulnerable populations, such as those in prison or working in the ‘gig’ economy. The contributors also consider appropriate responses across scales and time. In the first phase of the pandemic – and thanks largely to warnings from Chinese doctor Li Wenliang and staff at the World Health Organization (WHO) – the public health response was properly recognized as being the most immediate challenge. In subsequent phases, economic effects and interactions with public health and care systems assumed greater prominence. Both phases require appropriate responses and changes in governance, public policy (both locally and globally) and shifts in the culture of public responsibility. It is these issues and the responses that this book analyses.The pandemic is rapidly evolving and its multiple impacts across geographies and societies are, as yet, not fully clear. In the Global South, the impact is set to reshape life experiences in the long term, with more profound and complex implications, and with a depth and scale of disruption that demands unprecedented solidarity and international cooperation. If we are to build a more just and resilient world post- COVID- 19, we need to understand, debate and chart the issues involved and what effective responses are.
PUBLISHED
https://bristoluniversitypress.co.uk/covid-19-in-the-global-south
Bristol
Keywords: International Development; International Integration; COVID 19; Development; Health; Poverty